Modeling the Presence of Myelin and Edema in the Brain Based on Multi-Parametric Quantitative MRI - Warntjes, Marcel; Engström, Maria; Tisell, Anders; Lundberg, Peter (Frontiers in Neurology, 2016)
The aim of this study was to present a model that uses multi-parametric quantitative MRI to estimate the presence of myelin and oedema in the brain. The model relates simultaneous measurement of R1 and R2 relaxation rates and proton density to four partial volume compartments, consisting of myelin partial volume, cellular partial volume, free water partial volume and excess parenchymal water partial volume. The model parameters were obtained using spatially normalised brain images of a group of 20 healthy controls. The pathological brain was modelled in terms of the reduction of myelin content and presence of excess parenchymal water, which indicates the degree of oedema. The method was tested on spatially normalised brain images of a group of 20 age-matched multiple sclerosis (MS) patients. Clear differences were observed with respect to the healthy controls: the MS group had a 79 mL smaller brain volume (1069 vs. 1148 mL), a 38 mL smaller myelin volume (119 vs. 157 mL) and a 21 mL larger excess parenchymal water volume (78 vs. 57 mL). Template regions of interest of various brain structures indicated that the myelin partial volume in the MS group was 1.6±1.5% lower for grey matter (GM) structures and 2.8±1.0% lower for white matter (WM) structures. The excess parenchymal water partial volume was 9±10% larger for GM and 5±2% larger for WM. Manually placed ROIs indicated that the results using the template ROIs may have suffered from loss of anatomical detail due to the spatial normalization process. Examples of the application of the method on high-resolution images are provided for three individual subjects, a 45-year-old healthy subject, a 72-year-old healthy subject and a 45-year-old MS patient. The observed results agreed with the expected behaviour considering both age and disease. In conclusion, the proposed model may provide clinically important parameters such as the total brain volume, degree of myelination and degree of oedema, based on a single qMRI acquisition with a clinically acceptable scan time.